Abrus agglutinin stimulates BMP‐2‐dependent differentiation through autophagic degradation of β‐catenin in colon cancer stem cells. Issue 5 (14th March 2018) - Panda, Prashanta K.; Naik, Prajna P.; Praharaj, Prakash P.; Meher, Biswa R.; Gupta, Piyush K.; Verma, Rama S.; Maiti, Tapas K.; Shanmugam, Muthu K.; Chinnathambi, Arunachalam; Alharbi, Sulaiman A.; Sethi, Gautam; Agarwal, Rajesh; et al.
Abstract : Eradicating cancer stem cells (CSCs) in colorectal cancer (CRC) through differentiation therapy is a promising approach for cancer treatment. Our retrospective tumor‐specimen analysis elucidated alteration in the expression of bone morphogenetic protein 2 (BMP‐2) and β‐catenin during the colon cancer progression, indicating that their possible intervention through "forced differentiation" in colon cancer remission. We reveal that Abrus agglutinin (AGG) induces the colon CSCs differentiation, and enhances sensitivity to the anticancer therapeutics. The low dose AGG (max. dose = 100 ng/mL) decreased the expression of stemness‐associated molecules such as CD44 and β‐catenin in the HT‐29 cell derived colonospheres. Further, AGG augmented colonosphere differentiation, as demonstrated by the enhanced CK20/CK7 expression ratio and induced alkaline phosphatase activity. Interestingly, the AGG‐induced expression of BMP‐2 and the AGG‐induced differentiation were demonstrated to be critically dependent on BMP‐2 in the colonospheres. Similarly, autophagy‐induction by AGG was associated with colonosphere differentiation and the gene silencing of BMP‐2 led to the reduced accumulation of LC3‐II, suggesting that AGG‐induced autophagy is dependent on BMP‐2. Furthermore, hVps34 binds strongly to BMP‐2, indicating a possible association of BMP‐2 with the process of autophagy. Moreover, the reduction in the self‐renewal capacity of the colonospheres was associated with AGG‐augmented autophagic degradation of β‐catenin through an interaction with the autophagy adaptor protein p62. In the subcutaneous HT‐29 xenograft model, AGG profoundly inhibited the growth of tumors through an increase in BMP‐2 expression and LC3‐II puncta, and a decrease in β‐catenin expression, confirming the antitumor potential of AGG through induction of differentiation in colorectal cancer.